Search for neutral higgs bosons in Multi-b-Jet events in pp̄ collisions at s=1.96TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (American Physical Society (APS), 2008)
Data recorded by the D0 experiment at the Fermilab Tevatron Collider are analyzed to search for neutral Higgs bosons produced in association with b quarks. This production mode can be enhanced in the minimal supersymmetric standard model (MSSM). The search is performed in the three b quark channel using multijet triggered events corresponding to an integrated luminosity of 1fb-1. No statistically significant excess of events with respect to the predicted background is observed and limits are set in the MSSM parameter space. © 2008 The American Physical Society.
Keywords: Data acquisition; Tellurium compounds; Fermilab Tevatron Collider; Integrated luminosities; Neutral Higgs bosons; Parameter spaces; Production modes; Supersymmetric standard models; Triggered events; Bosons